2011
DOI: 10.1016/j.juro.2011.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Changes in Young Adults Using Ketamine

Abstract: Ketamine users with at least a 2-year habit of 3 or more hits per week have altered bladder function that can be recognized and that causes bother. These early functional changes have the potential to normalize after 1 year of ketamine abstinence. This study provides a basis for the development of health promotion material that can be used in the community by welfare workers seeking to encourage drug cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 12 publications
4
44
0
1
Order By: Relevance
“…Concerning the duration of ketamine abuse and the development of ketamine cystitis, our data found the median years of exposure was 4 for our cohort in which 92 % of them have features of ketamine cystitis. Another study in Hong Kong found that a ketamine abuser with at least 2 years of exposure (more than three uses per week) had significantly lower voided volume and higher scores in the Pelvic Pain, Urgency and Frequency questionnaire, which is comparable with our clinical experience [7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Concerning the duration of ketamine abuse and the development of ketamine cystitis, our data found the median years of exposure was 4 for our cohort in which 92 % of them have features of ketamine cystitis. Another study in Hong Kong found that a ketamine abuser with at least 2 years of exposure (more than three uses per week) had significantly lower voided volume and higher scores in the Pelvic Pain, Urgency and Frequency questionnaire, which is comparable with our clinical experience [7].…”
Section: Discussionsupporting
confidence: 83%
“…A recent study of 66 ketamine abusers found that the voided volume was significantly higher for those who quitted ketamine for more than 1 year than those who still abused ketamine or stopped it for less than 3 months [7].…”
Section: Discussionmentioning
confidence: 97%
“…By alteration of the epithelial cell-to-cell adhesion and cell coupling in the renal tract, ketamine causes damage through a nonclassical profi brotic mechanism. Ketamine abuse more than three times weekly for more than 2 years has been found to be a signifi cant risk factor for urinary tract disease (9). Although recovery is observed in most cases with an early intervention, irreversible damage may occur in chronic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ketamine 3 or more times a week was associated with measurable dysfunction in terms of LUTS, which could persist for up to 1 year after drug cessation, whilst contracted, thick-walled, and painful bladders often developed after the onset of frequency and urgency. 43 Upper tract involvement was thought to be due to long-term decrease in bladder capacity, but this conclusion is now challenged. Ketamine users tended to be experienced poly-drug users; 80% of subjects reporting such poly-use, and two thirds of them said they also consumed alcohol when they took ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine users tended to be experienced poly-drug users; 80% of subjects reporting such poly-use, and two thirds of them said they also consumed alcohol when they took ketamine. 43 According to a large population survey published in 2012, 6 98% ketamine users were reported to be concomitant with alcohol use, 96% with 3,4-methylenedioxymethamphetamine (MDMA), 92% with cannabis, 79% with cocaine, 78% with tobacco, 67% with mephedrone, 32% with amphetamine, and 28% with isopropyl nitrate.…”
Section: Discussionmentioning
confidence: 99%